2014
DOI: 10.1016/j.juro.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus is Independently Associated with an Increased Risk of Mortality in Patients with Clear Cell Renal Cell Carcinoma

Abstract: Our results suggest that diabetes mellitus is independently associated with decreased cancer specific and overall survival in patients with surgically treated clear cell renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
1
18
0
7
Order By: Relevance
“…Recent meta-analysis suggested that DM increases risk of kidney cancer [28]. Moreover, Psutka et al [29] showed DM patients had worse cancer-specific survival and overall survival after surgery for clear cell-type RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis suggested that DM increases risk of kidney cancer [28]. Moreover, Psutka et al [29] showed DM patients had worse cancer-specific survival and overall survival after surgery for clear cell-type RCC.…”
Section: Discussionmentioning
confidence: 99%
“…We includedclearcell,papillary,chromophobe, collecting duct, and unspecified RCC histologies and excluded oncocytoma (11). TNM stage (2010 criteria) and Fuhrman grade (1)(2)(3)(4) or differentiation (well, moderately,poorly,andundifferentiated)were obtained from pathology reports.…”
Section: Ascertainment Of Rcc and Deathmentioning
confidence: 99%
“…ccRCC is responsible for the most cancer-related deaths class accounts for 70À85% of RCC [3]. RCC is considered a metabolic disease [4À6], and obesity and atherosclerosis have been reported to be risk factors for RCC [7,8]. ccRCC is known for abnormal lipid accumulation [4] of cholesterol, cholesterol esters, and neutral lipids (triglycerides) [9].…”
Section: Introductionmentioning
confidence: 99%